2016
DOI: 10.1149/2.0551607jes
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Electrodeposited Porous ZnO Thin Film Based Immunosensor for Detection ofVibrio choleraeToxin

Abstract: Here, we have reported one step fabrication of a porous thin film of the zinc oxide nanoparticles (ZnO NPs) directly onto the indium tin oxide (ITO) glass substrate by cathodic electrodeposition from an aqueous solution containing zinc nitrate. The morphological studies of a thin film of ZnO NPs suggest that the NPs formed a porous structure with irregular pore size distribution over the surface of ITO glass substrate. The average pore size and wall thickness of pores obtained as 620 nm and 50-120 nm, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 39 publications
2
16
2
Order By: Relevance
“…Both immunosensors gave satisfactory LoD with the GCE-PAN-Ab-BSA giving the least LoD of 3.2 × 10 −13 g / mL compared to that of the GCE-PAN@FePc-Ab-BSA of 2.0 × 10 −12 g/mL. As compared in Table 2 , only few reports gave lower LoD of ~ 10 −15 g/mL [ 10 ] and ~ 10 −17 g/mL [ 15 ], while the LoDs obtained in this work are comparable or even better than some reports [ 9 , 11 14 ].…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…Both immunosensors gave satisfactory LoD with the GCE-PAN-Ab-BSA giving the least LoD of 3.2 × 10 −13 g / mL compared to that of the GCE-PAN@FePc-Ab-BSA of 2.0 × 10 −12 g/mL. As compared in Table 2 , only few reports gave lower LoD of ~ 10 −15 g/mL [ 10 ] and ~ 10 −17 g/mL [ 15 ], while the LoDs obtained in this work are comparable or even better than some reports [ 9 , 11 14 ].…”
Section: Resultssupporting
confidence: 75%
“…Surprisingly, this finding has rarely been reported in any BSA-incorporated electrochemical immunosensors. For example, Gupta et al [ 11 ] observed higher electron transfer rate constants (high-rate constant) with ITO-ZnO-Ab-BSA immunosensor than the corresponding electrodes without BSA (i.e., ITO-ZnO or ITO-ZnO-Ab) and attributed the finding only to the porous nature of the electrode surface. Similar to our case, PAN@FePc is more porous than the PAN (see BET data in Table 1 ), but we believe that the redox kinetics of BSA in the presence of FePc is beyond the porous nature of the PAN@FePc electrode.…”
Section: Resultsmentioning
confidence: 99%
“…We found that the magnitude of the current increased with increasing Vc T concentration. This increase in the magnitude of the current revealed the formation of an antigen–Ab complex by probing the features of the interfacial properties; the complex acted as an electron‐transfer accelerating layer for redox species on the immunoelectrode surface . Moreover, this might have been due to the fact that when Vc T interacted with the Ab/PANnf/ITO immunoelectrode, the resulting surface charge of the immunoelectrode became quite different from that of the individual Ab or Vc T. This change in the surface energy was related to the electrochemical response .…”
Section: Resultsmentioning
confidence: 99%
“…Label-free and single-immunoreaction biosensors have been reported using electrode substrates nanostructured with PPI-AuNP nanocomposite [ 81 ], PANnf’s [ 82 ], ZnO NPs [ 83 ], CNTs [ 84 ] and CNFs [ 85 ] for Vibrio cholerae [ 82 ] and its characteristic toxins [ 81 , 82 , 85 ] or antibodies [ 84 ]. Although all these immunosensors exhibit good analytical characteristics in terms of sensitivity and selectivity, none has been applied to the analysis of real samples.…”
Section: Selected Nanostructures In Electrochemical Biosensing Formentioning
confidence: 99%